Monitoring American woodcock abundance in Tennessee using automated recording units - Evan J. Buck; David A. Buehler (Wildlife Society Bulletin)
Abstract Although American woodcock (Scolopax minor) have been declining for the past 50 years, their breeding activity is not regularly monitored across much of the southeastern United States. Due to predictable crepuscular display behaviors, woodcock are a good candidate for monitoring with automated recording units (ARUs). Here, we test the efficacy of ARUs for monitoring woodcock against human observers. We also evaluate the use of automated detection software for 2 woodcock display sounds, the peent call and twitter display, and estimate whether abundance estimates can be derived from the acoustic data. We find that human observers detected more woodcock and counted more twitter displays than ARUs with manual human review but counted similar numbers of peent calls. The automated detection program monitoR successfully classified 52% of peent calls captured in recordings but was unable to consistently classify twitter displays. We were unable to successfully predict the number of woodcock in a given area based on the total number of peents or twitters recorded per survey by human observers in the field. Automated recording units can be effectively used to monitor woodcock presence but have limitations compared to human observers for estimating abundance.